Does Forward Guidance Matter in Small Open Economies? Examples from Europe - Jakub Rybacki (Econometric Research in Finance, 2019)
The effect of forward guidance on interest rate expectations in small, open economies is often described as heterogeneous. There are examples when financial markets adjusted term structure to reflect interest rate forecasts provided in the projections published by the central banks. On the other hand, medium-term expectations can persistently deviate from trajectories presented by decision-makers, influenced by foreign monetary policy. Our aim is to find the maximal forecast horizon where the domestic forward guidance of local banks in European economies affects market interest rate expectations strongly as compared to the ECB policy. We analyzed the term structure of interest rates in Sweden, Norway, and the Czech Republic. Central banks in these three economies provide the most mature forward guidance, e.g., regularly publishing interest rate forecasts with detailed discussions. The three-month interbank rate path calculated with the Nelson-Siegel model was contrasted with both the trajectory of policy rates presented in central bank projections and that implied by the three-month EURIBOR. We found that interest rate expectations were more influenced by ECB policy than by domestic assumptions when the forecast horizon exceeds four quarters.